2009
DOI: 10.1007/s00280-009-1065-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampin on the pharmacokinetics of Axitinib (AG-013736) in Japanese and Caucasian healthy volunteers

Abstract: PurposeAxitinib, a potent and selective inhibitor of vascular endothelial growth factor receptors 1, 2, 3, is metabolized by cytochrome P450 3A4 and glucuronidation. This study evaluated the effect of rifampin, a potent inducer of drug-metabolizing enzymes, on axitinib plasma pharmacokinetics. Equal numbers of Japanese and Caucasian subjects were enrolled to assess the potential differences in axitinib pharmacokinetics between the two ethnicities.MethodsForty healthy volunteers were randomized to receive 5 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 21 publications
(18 reference statements)
2
43
0
Order By: Relevance
“…In a phase I two-way crossover study of axitinib given with or without rifampicin in Japanese and Caucasian healthy volunteers (n = 40), rifampicin (a potent inducer of drugmetabolizing enzymes including CYP3A4, CYP1A2, and UGT1A1) decreased the AUC from time zero extrapolated to infinity (AUC ¥ ) and C max of axitinib (geometric mean reduced to 79% and 71%, respectively). [53] No differences in pharmacokinetics were observed between Japanese and Caucasian subjects.…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…In a phase I two-way crossover study of axitinib given with or without rifampicin in Japanese and Caucasian healthy volunteers (n = 40), rifampicin (a potent inducer of drugmetabolizing enzymes including CYP3A4, CYP1A2, and UGT1A1) decreased the AUC from time zero extrapolated to infinity (AUC ¥ ) and C max of axitinib (geometric mean reduced to 79% and 71%, respectively). [53] No differences in pharmacokinetics were observed between Japanese and Caucasian subjects.…”
Section: Pharmacokineticsmentioning
confidence: 97%
“…In vitro studies suggested that CYP3A was responsible for substrate consumption of axitinib in human liver microsomes (Zientek et al, 2010). The role of CYP3A in the metabolism of axitinib was supported by results from clinical drug interaction studies where ketoconazole increased the axitinib plasma AUC ratio relative to a control arm by 2-fold and rifampin pretreatment decreased this ratio to 0.2 (Pithavala et al, 2010(Pithavala et al, , 2012b.…”
Section: Introductionmentioning
confidence: 57%
“…Following the administration of ketoconazole, a 2-fold increase in the AUC of axtinib 5 mg was observed . Furthermore, administration of rifampin decreased the AUC of axitinib 5 mg by 79% (Pithavala et al, 2010). Since ketoconazole is a strong inhibitor of CYP3A and rifampin is a strong inducer of both CYP3A and UGT1A1, the in vitro phenotyping, enzyme kinetics, and UGT1A1-genotyped HLM in vitro studies, accompanied by knowledge of the absolute bioavailability (58%) of axitinib, support the impact of CYP3A4 on the findings of clinical drug-drug interaction studies.…”
Section: Discussionmentioning
confidence: 82%
“…The mass balance following an oral dose of 5 mg [ pharmacologically inactive, were observed in human plasma, axitinib N-glucuronide (M7) and axitinib sulfoxide (M12), accounting for 50.4% and 16.2% of circulating radioactivity, respectively. Clinical drug interaction studies with axitinib as an object or victim drug have been conducted in combination with ketoconazole and rifampin as strong inhibitors and inducers, respectively, of CYP3A and the respective changes in axitinib plasma exposure suggested a predominant role for CYP3A in the clearance of axitinib since ketoconazole increased the area under the plasma versus time curve (AUC) ratio relative to control by 2.1-fold and rifampin pretreatment decreased this AUC ratio to 0.21 (Pithavala et al, 2010. The axitinib plasma exposure in cancer patients is variable (e.g., interindividual variability expressed as %CV is on the order of ;80%), but has been effectively addressed in the clinic by use of a dose-tolerability titration schedule that essentially normalizes patient exposure over a dose range from 2 to 20 mg/day [Pfizer Laboratories, 2012, prescribing information for Inlyta (axitinib) tablets for oral administration] (Chen et al, 2013;Rini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%